A review of literature on the effects of road hump on traffic speed and traffic noise in institutional area - Mustafa, Nur Asiah; Kadar Hamsa, Abdul Azeez (2018)
Traffic speed and noise are the major transport-related determinants in affecting the quality of learning and research environment in a University. The calm and safe environmental set-up of a University is very crucial in creating a conducive learning and research atmosphere on-campus. The increasing number of private vehicles on-campus has resulted in the increase in speed and noise level and thus has attributing towards an increase in environmental pollution on-campus. Road humps are considered effective as a traffic calming measure in reducing speed and noise level of the moving vehicles. However, the imminent reduction in the speed of the vehicles depends very much on the profiles of a road hump in terms of its width, length and height. The difference in the profiles of the road hump will cause changing driving behavior of the users, especially when approaching a road hump. Thus, this paper is part of the ongoing study to analyse the effectiveness of road hump as a traffic calming measure in the campus area. The literature on traffic calming in Malaysia is highlighted in this paper.